2008
DOI: 10.1074/jbc.m801876200
|View full text |Cite
|
Sign up to set email alerts
|

Basigin-2 Is a Cell Surface Receptor for Soluble Basigin Ligand

Abstract: The metastatic spread of a tumor is dependent upon the ability of the tumor to stimulate surrounding stromal cells to express enzymes required for tissue remodeling. The immunoglobulin superfamily protein basigin (EMMPRIN/CD147) is a cell surface glycoprotein expressed by tumor cells that stimulates matrix metalloproteinase and vascular endothelial growth factor expression in stromal cells. The ability of basigin to stimulate expression of molecules involved in tissue remodeling and angiogenesis makes basigin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
101
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 38 publications
4
101
0
Order By: Relevance
“…5C). The results of some previous studies suggest strongly that high levels of glycosylation are necessary for induction of MMP production (Guo et al, 1997;Tang and Hemler, 2004), whereas others have demonstrated robust MMP production after treatment with nonglycosylated CD147 (Belton et al, 2008) or CD147 substituted only with the disaccharide, chitobiose (Kawakami et al, 2011). Clearly, further investigation is required to elucidate the role of glycosylation in CD147 activities in different contexts.…”
Section: Discussionmentioning
confidence: 87%
“…5C). The results of some previous studies suggest strongly that high levels of glycosylation are necessary for induction of MMP production (Guo et al, 1997;Tang and Hemler, 2004), whereas others have demonstrated robust MMP production after treatment with nonglycosylated CD147 (Belton et al, 2008) or CD147 substituted only with the disaccharide, chitobiose (Kawakami et al, 2011). Clearly, further investigation is required to elucidate the role of glycosylation in CD147 activities in different contexts.…”
Section: Discussionmentioning
confidence: 87%
“…Basigin‐2 (NM_198589) is a major isoform of basigin, and it is ubiquitously expressed. While basigin‐1 transcript (NM_001728), with a third immunoglobulin domain (Ig0), is only expressed specifically in the retinal photoreceptors 19, 26, 27. Basigin‐1, associating with a protein secreted from rods, being named as rod‐derived cone viability factor (RdCVF) and glucose transporter (Glut)‐1, form a complex at the cone surface to increase glucose uptake and promotes cone survival 28, 29.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 was initially identified as an inducer of the expression of MMPs, including MMP-1, -2, -3, -9, and -11, in co-cultured tumor cells and fibroblasts. Several studies have shown that soluble CD147 is capable of inducing MMP production in fibroblasts expressing CD147, as well as in tumor cells (Belton et al, 2008). The fact that CD147 is overexpressed in a number of carcinoma tissues, coupled with its ability to stimulate MMP secretion, suggests that it serves as a key regulator of oncogenesis (Iacono et al, 2007).…”
Section: Discussionmentioning
confidence: 99%